Pelatihan Penerapan Supply Chain Management untuk Meningkatkan Produktivitas Printing Sepatu - Almahdy, Indra; Lesmana, Sakti Aji (CV. IRA PUBLISHING, 2024)
The formation of several small, medium and large scale industries shows that Indonesia's industrial growth is increasing. Society is impacted positively and negatively by this increase. Small businesses should strive to improve supply chain efficiency. The supply chain involves all parties directly and indirectly to meet customer demand. Maximizing total value is the goal of the supply chain. The difference between the value of the final product received from the customer and the supply chain effort (cost) invested to meet customer demand constitutes the total value of the supply chain. Manufacturing processes in the production process, transportation networks that deliver products from factories to retail stores, and warehouses where products are stored in distribution facilities where large shipments are divided into smaller lots and returned. This training on supply chain management by considering environmental factors aims to increase productivity by minimizing waste produced, optimizing usage and supply chains in accordance with industrial needs. So that at the end of the training participants can have ideas for better time management based on the design cycle to delivery distribution and feedback.